THE INFLUENCE OF ORGANIZATIONAL COMMITMENT AND ETHICS CLIMATE ON EMPLOYEE PERFORMANCE OF EL FAJR HOUSE OF EDUCATION FOUNDATION PALEMBANG - Malikal Mulki Octadyla; Sayyid Muhammad Abdurrahman; Cindi Pramita; Muhammad Rusdi (Jurnal Ekonomi, 2023)
The implementation of Good Corporate Governance is very important in carrying out good corporate governance, including in local tax management practices. The principles of Good Corporate Governance also act as a controller for the government to run a good government and free from corruption, collusion and nepotism. The purpose of this study is to propose a research model on the factors that influence the improvement of the quality of employee performance through the application of Good Corporate  Governance  principles.  A  review  of  the  relevant  literature indicates that independence, transparency, accountability, responsibility, and obligation are determining factors in explaining or defining Good Corporate Governance. Meanwhile, employee performance can be explained from performance planning, performance implementation, performance measurement, performance appraisal, and performance evaluation. The theoretical implication in this study is to improve the quality of pre-existing employee performance in the form of a company.